2012
DOI: 10.1007/s10853-012-6475-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations and segregation in Fe–Ni alloys and nanoalloys

Abstract: Ordering and segregation properties of Fe-Ni alloys and nanoalloys are investigated by means of Metropolis Monte Carlo (MMC) and molecular dynamics (MD) simulations. The model is based on an embedded atom potential which, according to thermodynamic integration, only stabilizes those phases that are observed experimentally. This stability is confirmed by MMC and the same phases are found stable in truncated octahedral nanoparticles containing no more than 201 atoms. At given composition, Ni segregates at {100} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In fact, as shown in Figure 5 c, the diffraction peak related to the crystallographic plane (111) of the FCC crystals did not show a splitting behavior compared with that observed in Section 3.1 . Since the metastable BCC Fe phase is more stable than the primary metastable FCC Fe crystals at moderate temperatures [ 42 , 44 ], the pre-existing metastable FCC crystals in the amorphous matrix for the ACR samples gradually transformed into the metastable BCC phase after heating to 786 K, confirming the metastable nature of the primary FCC phase at room temperature and the abnormal increase of the released heat enthalpy for the ACR samples during crystallization below T s . However, upon increasing to 852 K, the newly-generated metastable BCC phase tended to transform back to two types of stable FCC Fe(Co) and FCC Ni(Si) phases accompanied by the formation of (Fe,Co) 2 B and Ni 31 Si 12 crystals in the ACR samples.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, as shown in Figure 5 c, the diffraction peak related to the crystallographic plane (111) of the FCC crystals did not show a splitting behavior compared with that observed in Section 3.1 . Since the metastable BCC Fe phase is more stable than the primary metastable FCC Fe crystals at moderate temperatures [ 42 , 44 ], the pre-existing metastable FCC crystals in the amorphous matrix for the ACR samples gradually transformed into the metastable BCC phase after heating to 786 K, confirming the metastable nature of the primary FCC phase at room temperature and the abnormal increase of the released heat enthalpy for the ACR samples during crystallization below T s . However, upon increasing to 852 K, the newly-generated metastable BCC phase tended to transform back to two types of stable FCC Fe(Co) and FCC Ni(Si) phases accompanied by the formation of (Fe,Co) 2 B and Ni 31 Si 12 crystals in the ACR samples.…”
Section: Resultsmentioning
confidence: 97%
“…In our case, with the gradual precipitation of FCC crystals within the BCC crystals, the element Ni were gradually isolated from BCC crystals, leading to the formation of the newly-generated FCC Ni(Si) phase. In fact, M. Byshkin et al has proven that the element Ni is easy to segregate from the Fe-rich BCC phases, resulting in the formation of the FCC phase [ 44 ]. The dissolution of a large amount of atoms Si in FCC Ni crystals would induce a large lattice distortion, possibly leading to the formation of nano twinning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the alloy without La-substitution, after annealing at 973 K, a small amount of intermetallic compounds was detected, indexed as Ni 31 Si 12 phase. Previous research has demonstrated that the Ni element is easy to segregate from Fe-rich bcc phases, resulting in the formation of fcc phase, and the over-saturated Si in Ni may form the Ni-Si intermetallic compounds [29,30]. However, after La addition, no Ni 31 Si 12 phase was detected in annealed samples.…”
Section: Resultsmentioning
confidence: 98%
“…The predicted trend for the MCA energy is also in line with experimental studies, where tetragonal L1 0 -ordered FeNi films were stabilized using the alternate deposition of Fe and Ni monatomic layers 23 . Furthermore, an extensive theoretical work has been done about phase stability 24 , phase transformation, segregation effects 25 and coercivity improvement through nano-structuring in FeNi alloys 26 . Theoretical works support that structural parameters of the FeNi alloy significantly depend on the Fe/Ni ratio as the Young’s modulus of the bcc Fe increases by enhancing the concentration of nickel 27 .…”
Section: Introductionmentioning
confidence: 99%